HOW DEVELOPING COUNTRIES CAN BENEFIT FROM INTELLECTUAL PROPERTY: THE ROLE OF COLLECTIVE MARKS IN TOURISM - GHAFELE, Roya (Journal of Environmental Management and Tourism; Vol 2 No 2 (2011): JEMT Volume II Issue 2(4) Winter 2011, 2011)
While tourism has been praised by a variety of international organizations as a means to promote the local economy in developing countries, tourism led growth has never been seen to be supported by a developing countries’ intellectual property regimes. Intellectual property rights, particularly if owned collectively, accelerate cluster creation, an organizational form particularly beneficial for tourism. The positive externalities associated with clusters can be reinforced through the assignment of collective marks. A region’s intangible assets, its social cohesion, can be fostered through the introduction of collective marks, since it is an intellectual property rights that can be owned collectively by a given community. This paper is one of the first of its kind to flesh out a more differentiated economic value proposition of collective marks, while at the same time illustrating the economic opportunities that the intellectual property system provides to developing countries’ economies.